Fabricação e caracterização de células solares de CdTe/CdS com eletrólito polimérico - Moreira, Raquele Lima (2017)
The current work aimed the fabrication and characterization of CdTe/CdS solar cells with polymeric electrolyte. The main component of the electrolyte was polyaniline, a conductive polymer that has been investigated as a counter electrode in dye-sensitized solar cells. The adopted deposition techniques were chemical bath and pulsed electrodeposition to obtain CdS and CdTe films which worked as the optical window and the cell absorber layer, respectively. Both techniques revealed to be very efficient, producing films with low material and energy expenses. The films were deposited on FTO conductive glass, with resistances between 9Ω and 11Ω. The voltammetric tests detected CdTe deposition in negative potentials, with cathodic current peaks in potentials between - 0.7 V and - 0.3 V and anodic current peaks about + 0.75 V. The pulsed electrodeposition with current periodic reversion adopted the cathodic potential of -0.6 V and the anodic potential of +0.2 V to the CdTe formation, resulting in films with nodular morphology, hexagonal structure, p-type conductivity and 2 eV band gap. The deposited CdS films presented small thickness and good substrate adherence, cubic structure, 55% to 60% optical transmittance in the visible area of the spectrum and 2.35 of band gap. The polyaniline was obtained in its emeraldine salt conductive form. The FTIR identified the PANI conductive phase characteristic peaks, indicating a well succeed polymerization. The electrolyte was fabricated from the PANI and the lithium perchlorate dispersion in chitosan. From the obtained films were assembled solar cells with approximately 1cm2. The cell electrical parameters were determined by the plot of the current-tension curves. The cell which presented the best results had short circuit current density of 0.136 mA/cm2, open circuit tension of 400 mV, maximum power of 0.021 mW/cm2 and efficiency of 20.2 x 10-3 %. These low values were assigned to the presence of cell intern resistances.